The consensus of integrative diagnosis and treatment of acute pancreatitis‐2017. Issue 1 (26th February 2019) - Li, Junxiang; Chen, Jing; Tang, Wenfu
Abstract: Acute pancreatitis (AP) is one of the most common acute abdominal diseases. The digestive disease committee, Chinese Association of Integrative Medicine, released Integrated traditional Chinese and Western medicine for diagnosis and treatment of acute pancreatitis in 2010. 1 Since then, further studies and great progress have been made by domestic and foreign counterparts from the perspective of both Chinese and Western medicine in AP, including the classification, fluid resuscitation, organ function maintenance, surgery intervention, enteral nutrition (EN), and syndrome differentiation and treatment. It is necessary to update the consensus on diagnosis and treatment of integrated Chinese and Western medicine to meet clinical needs. Therefore, the 2012 Revision of the Atlanta Classification Standard (RAC) by the International AP Consensus, 2 the 2013 the Management of Acute Pancreatitis by the American College of Gastroenterology, 3, 4 the 2014 Guidelines for diagnosis and treatment of the acute pancreatitis guide (2014) by the Chinese medical association branch, 5 the 2014 Guidelines on Integrative Medicine for Severe Acute Pancreatitis by the General Surgery Committee of the Chinese Society of Integrated Traditional Chinese and Western Medicine, 6 and Traditional Chinese Medicine Consensus on the Diagnosis and Treatment for Acute Pancreatit is by the Spleen and Stomach committee of China Association of Traditional Chinese Medicine 7, 8 were taken into account for the revision of the consensus published in 2010. The digestive specialists in Chinese and Western medicine had a discussion on traditional Chinese medicine (TCM) types, syndrome differentiation, the main points of integrative medicine, and so on. According to the Delphi method, Consensus of Integrative Diagnosis and Treatment of Acute Pancreatitis (the 2017 revision) has been passed after three rounds votes. (The voting options are as follows: (a) totally agree; (b) agree, but with some reservations; (c) agree, but with larger reservations; (d) disagree, but reserved; and (e) absolutely disagree. If more than two out of three choose (a), or over 85% choose (a) + (b), the consensus will be passed.) The final validation was carried out by the core expert group in Taizhou, Jiangsu on June 9, 2017. The full text is as follows.